PERAN KOMUNIKASI KELUARGA DALAM PEMBENTUKAN IDENTITAS REMAJA - Banilla Rahmadhania (Cahaya Ilmu Bangsa, 2024)
Family communication plays a crucial role in the adolescent identity formation process. Through healthy interactions and emotional support, families can help teenagers understand themselves and face social pressures from external environments. This study aims to explore the role of family communication in shaping adolescent identity through a qualitative approach. The study's respondents are adolescents aged 17-25 who actively communicate with their families. The findings indicate that effective family communication can help adolescents develop strong principles, self-confidence, and self-perception. Therefore, it is essential for parents to provide greater attention in supporting healthy and effective family communication.